DAMPAK HUJAN METEOR PADA KEMUNCULAN LAPISAN E-SPORADIS DI ATAS SUMEDANG (THE IMPACT OF METEOR SHOWERS ON THE OCCURRENCE OF E-SPORADIC LAYER OVER SUMEDANG) - Rhorom Priyatikanto; Farahhati Mumtahana; Mumen Tarigan (Jurnal Sains Dirgantara, 2017)
Meteor showers have been believed as one important source of metalic ion which is accumulated at ~100 km altitude and triggering the emergence of E-Sporadic layer. In this study, meteor showers catalogue derived from the observations in visual and radio windows were used to establish a model and temporal map of annual meteor showers expected to be observed in Sumedang, West Java. The map was compared to ionospheric observation data acquired in Sumedang throughout 2014-2015 in order to understand the relation between the showers of various fluxes to the occurrence of E-Sporadic layer. The analysis revealed that several meteor showers with geocentric speed of vG < 50 km/s possibly influence the occurrence of E-Sporadic layer, while the showers with vG > 50 km/s impact insignificantly. However, the seasonal variation of the percentage of E-Sporadic occurrence is far more dominant compared to its fluctuation during meteor showers.Abstrak Hujan meteor dengan fluks tinggi telah dipercaya sebagai salah satu sumber penting ion logam yang terkumpul pada ketinggian ~100 km dan memicu kemunculan lapisan E-Sporadis. Pada studi ini, katalog hujan meteor hasil pengamatan pada jendela visual dan radio digunakan untuk membangun model dan peta temporal hujan meteor tahunan yang diharapkan teramati di Sumedang, Jawa Barat. Peta tersebut dibandingkan dengan data pengamatan ionosfer di Sumedang sepanjang 2014-2015 untuk mengetahui keterkaitan antara hujan meteor dengan beragam fluks serta kemunculan lapisan E-Sporadis. Hasil analisis menunjukkan bahwa beberapa hujan meteor dengan kelajuan geosentris vG < 50 km/s memiliki indikasi berpengaruh pada kemunculan E-Sporadis, sementara hujan meteor dengan vG > 50 km/s tidak berdampak signifikan. Namun, variasi musiman dari persentasi kemunculan E-Sporadis jauh lebih dominan dibandingkan fluktuasinya saat hujan meteor.